2017
DOI: 10.18178/ijcea.2017.8.3.652
|View full text |Cite
|
Sign up to set email alerts
|

Isotherm Models of Heavy Metal Sorption onto Zinc-tricarboxylic

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
2
1
0
Order By: Relevance
“…While in the case of Pb, high removal efficiency of 90.13% was attained within 60 min. This finding is in good agreement with the result obtained by Kowsura et al (2017) on Pb removal from water using Zn 3 (BTC) 2 . Liu et al (2007) reported chromium removal with zero-valent iron decorant on a graphene nanosheet by using 1 g adsorbent dosage within 90 min has a removal efficiency of 70%.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 92%
“…While in the case of Pb, high removal efficiency of 90.13% was attained within 60 min. This finding is in good agreement with the result obtained by Kowsura et al (2017) on Pb removal from water using Zn 3 (BTC) 2 . Liu et al (2007) reported chromium removal with zero-valent iron decorant on a graphene nanosheet by using 1 g adsorbent dosage within 90 min has a removal efficiency of 70%.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 92%
“…6 ). Pb 2+ had a high removal efficiency of 90.13% at 60 min, matching the findings of Kowsura et al [ 76 ]. Cadmium (II) adsorption by Co-DPA has maximum removal efficiency of 92.85% which is the same as the result obtained by [ 74 ] with a maximum adsorption capacity of 33 mg/g at 80 min.…”
Section: Resultssupporting
confidence: 89%
“…Massively used compounds made by chemically like metal–organic network (MON) are thus made up of alloy ions/metallic ions and organic linkers. With the aid of the hydrothermal method, new MONs composed of zinc considered metal ions and benzene -dicarboxylic acid as the organic linker 3 . Biography of MONs is their superficial alteration and as well as their particle control six division 4 .…”
Section: Introductionmentioning
confidence: 99%